Hubungan internal locus of control dengan hasil belajar kognitif materi cahaya peserta didik kelas v sdn di kecamatan laweyan - Yulvia Zalza Bella; Matsuri Matsuri; Roy Ardiansyah (Didaktika Dwija Indria, 2025)
This research aims to determine the relationship between internal locus of control and cognitive learning outcomes regarding light material in class V students at elementary schools in Laweyan District. The cognitive domains in this research are analyzing, evaluating, and creating which are the domains of high order thinking skills. This research uses quantitative methods with a correlational research design. Research data collection uses tests and scales, with a cluster random sampling method for sampling. The analysis was carried out using a simple correlation coefficient. From the analysis carried out it can be concluded that there is a positive and significant relationship between internal locus of control and cognitive learning outcomes as indicated by the acquisition of a significance value of 3.221<4.07 with a Pearson correlation of 0.329